Reg4-Induced Mitogenesis Involves Akt-GSK3β-β-Catenin-TCF-4 Signaling in Human Colorectal Cancer - Bishnupuri, Kumar S (Mol Carcinog, 2013)
Upregulation of regenerating gene 4 (Reg4) is observed in many human gastrointestinal malignancies including colorectal cancer (CRC). We previously reported a Reg4-mediated induction of epidermal growth factor receptor-Akt-AP1 signaling regulating CRC cell apoptosis. However, the role of Reg4 in the regulation of CRC cell division is poorly understood. This study tests the hypothesis that Reg4 induces Akt-GSK3β-β-Catenin-TCF-4 signaling to regulate CRC cell division. In vitro models of human CRC were used to determine the role of Reg4 in regulation of CRC cell division. Cell cycle studies demonstrated that Reg4 treatment significantly decreased CRC cell number in G1 phase and increased in G2 phase. Subsequently Reg4 significantly increased the mitotic index of CRC cells. As assessed by real-time RT-PCR and Western blot analyses, Reg4 significantly increased the expression of cell cycle regulatory genes Cyclin D1 and D3, and associated Cyclin-dependent kinases (CDK4 and CDK6). Reg4-mediated increase in these genes involved a pathway that included an induced Akt activity by increasing phosphorylation of Thr308 and Ser473, a reduced glycogen synthase kinase 3β(GSK-3β) activity by increasing phosphorylation of Ser9, an induced nuclear translocation of β-Catenin by decreasing phosphorylation of Ser33/37/Thr41, and an increased TCF-4 transcriptional activity. Furthermore, antagonism of Reg4-signaling using Reg4-specific mAbs (2H6 and 3E5) and Akt inhibitor significantly decreased, whereas agonism using GSK-3β antagonist (SB216763) significantly increased mitotic index and proliferation of CRC cells. These results identify Reg4 as a key regulator of the CRC cell division and proliferation, hence a potential target of human CRC treatment.